2007
DOI: 10.1080/15512160701338320
|View full text |Cite
|
Sign up to set email alerts
|

Resolved: Academic Debate Should Be a Part of Political Science Curricula

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
15
0
3
Order By: Relevance
“…As a matter of fact, these abilities are features and elements of critical thinking skills (Rudd, 2007;Kosciulek & wheaton, 2003). Previous studies also confirm that in-class debate can cultivate, promote, and develop critical thinking skills (Zare & Othman, 2013;Alasmari & Ahmed, 2013;Doody & Condon, 2012;Omelicheva, 2007;Kennedy, 2007). In addition, preparing for debates helped improve superior mastery of the course contents.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As a matter of fact, these abilities are features and elements of critical thinking skills (Rudd, 2007;Kosciulek & wheaton, 2003). Previous studies also confirm that in-class debate can cultivate, promote, and develop critical thinking skills (Zare & Othman, 2013;Alasmari & Ahmed, 2013;Doody & Condon, 2012;Omelicheva, 2007;Kennedy, 2007). In addition, preparing for debates helped improve superior mastery of the course contents.…”
Section: Discussionmentioning
confidence: 65%
“…Participants expressed that engaging in debate encouraged them to explore the content of the course deeply, exposed them to many different perspectives, and hence assisted them to connect broadly to the content of the course. In her study, Omelicheva (2007) found that classroom debate helped the learners get involved in the intellectual practices which illustrate critical thinking skills. The participants of the study also stated that classroom debate provided an opportunity for them to practice and promote their presentation and teamwork skills.…”
Section: Classroom Debatementioning
confidence: 99%
“…All students would benefit from learning debating techniques and participating in formal debates". In some university courses, as Political Science, it seems obvious that academic debate should be a part of the curriculum (Omelicheva, 2007).…”
Section: Why Academic Debates?mentioning
confidence: 99%
“…Debat ternyata menjadi alat yang unggul dalam pembelajaran dan evaluasi. Metode debat bisa mengukur prestasi siswa, mendiagnosa masalah belajar, belajar lebih banyak tentang cara pandang dan sikap terhadap materi yang dipelajari (Omelicheva, 2007).…”
Section: Deferensiasi Gaya Belajar Divergen Dan Konvergen Danunclassified